2006
DOI: 10.1182/blood-2005-11-008151
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for subcomplexes in the Fanconi anemia pathway

Abstract: Fanconi anemia (FA) is a genomic instability disorder, clinically characterized by congenital abnormalities, progressive bone marrow failure, and predisposition to malignancy. Cells derived from patients with FA display a marked sensitivity to DNA cross-linking agents, such as mitomycin C (MMC). This observation has led to the hypothesis that the proteins defective in FA are involved in the sensing or repair of interstrand cross-link lesions of the DNA. A nuclear complex consisting of a majority of the FA prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
79
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 36 publications
(57 reference statements)
4
79
1
Order By: Relevance
“…Even though the FANCcore complex is assembled in the nucleus, several of the FANCcore complex proteins can be found in cytoplasmic subcomplexes. For example, FANCA has been isolated in association with FANCG, FANCB and FANCL, and FANCC interacts with a FANCE-FANCF subcomplex (Medhurst et al, 2006). Whether these subcomplexes directly or indirectly regulate independent pathways involved in protein PTM remains to be determined in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the FANCcore complex is assembled in the nucleus, several of the FANCcore complex proteins can be found in cytoplasmic subcomplexes. For example, FANCA has been isolated in association with FANCG, FANCB and FANCL, and FANCC interacts with a FANCE-FANCF subcomplex (Medhurst et al, 2006). Whether these subcomplexes directly or indirectly regulate independent pathways involved in protein PTM remains to be determined in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Certain components of the FA core complex also form distinct subcomplexes among themselves or with factors outside the core complex (3,8,9). For example, it has been reported that the members of the eight-component FA core complex form two discrete subcomplexes, one composed of FANCA, FANCB, FANCG, FANCL, and FANCM, and the other consisting of FANCC, FANCE, and FANCF (9). Outside the FA core complex, FANCA, FANCC, and FANCG are found to associate with a variety of cellular factors that primarily function in redox-related processes (30).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the core complex components also form distinct subcomplexes among themselves or with factors outside the core complex (3,8,9). The function of these FA subcomplexes has yet to be elucidated.…”
mentioning
confidence: 99%
“…An increasing number of FA genes have been identified and their allelic products are interconnected with other DNA damage response proteins involved with genomic stability and tumorigenesis (4,5). www.bjournal.com.br have a comprehensive diagnosis of this disease (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…A general model has been proposed for the FA pathway based on the response to DNA after exposure of cells to genotoxic stress or following replication arrests (22,23). In brief, eight of the cloned FA genes encode for proteins (FANCA, B, C, E, F, G, L, M), which are part of a large nuclear core complex with multiple subunits and E3 ubiquitin ligase activity (5,24). The activation of this complex induced by DNA replication or by DNA-damage results in monoubiquitination of FANCD2, which moves into areas of damaged chromatin to interact with downstream FA members (FANCD1/BRCA2, FANCJ, FANCN) and other DNA-repair proteins such as BRCA1 and RAD51.…”
Section: Introductionmentioning
confidence: 99%